POLICE THEORY AND HISTORY: PHILOSOPHICAL FOUNDATIONS, EUROPEAN MODELS AND DEVELOPMENT IN BRAZIL - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
The theory and practice of modern policing emerge from the development of the national state and its philosophical foundations, especially from modern contractualist thinking. The objective is to understand the historical construction of the police function in the context of the modern state, its dilemmas between security and freedom, and its evolution as an instrument of social control and urban organization. At the institutional level, the construction of the police occurred differently in France, England, Portugal, and, later, in Brazil. Traditionally, studies on the history of the Brazilian police have emphasized Rio de Janeiro as a center of institutional models, generating what has been conventionally called “bandeirantismo”. This article seeks to reevaluate this historiographical approach by highlighting the formation of the General Intendancy of the Police of São Paulo, proposing the concept of “police bandeirantismo” as an interpretative key to understanding the local specificities of the police organization in the province of São Paulo. The main objective is to analyze the police function in the context of the modern state and its dilemmas between guaranteeing security and preserving civil liberties. The research adopts a qualitative approach, of a historical-interpretative nature, based on a bibliographic review and documentary analysis. Classic authors of political theory (Hobbes, Locke, Rousseau), public security theorists (Beccaria, Foucault, Monjardet and Cerqueira) are mobilized, as well as primary and secondary sources of Portuguese-Brazilian historiography on the police forces of the 18th and 19th centuries. The study identifies that the French model of policing, centralized and authoritarian, strongly influenced Portugal and, consequently, Brazil. However, in São Paulo, the institutional development of the police also reflected its own characteristics, linked to the bandeirante tradition, local autonomy and administrative pragmatism. These specificities show a parallel trajectory to that of Rio de Janeiro, indicating that the São Paulo model was not a mere replica, but rather an expression of a regional project of security and social control. The history of the police in Brazil cannot be explained solely from the experience of Rio. The case of São Paulo, linked to the so-called “police bandeirantism”, points to the need to decentralize the historiographical analysis and recognize the multiple forms of police institutionalization in the country. The police, as an instrument of the modern State, remains marked by the tension between the legitimate use of force and the preservation of civil rights — a dilemma that has permeated its historical trajectory to the present day.